Information Systems and Tax Online in Indonesia, Effect Decrease in Rate, Audit and Organizationâ€™s Culture Against Tax Revenue on Foreign Investment Office - ., Hartono; Halim, Paisal; Badruddin, Syamsiah; Hendarso, Panji; ., Yulianto; Ikhsan Setiawan, Muhammad; Saleh A., A (International Journal of Engineering and Technology, 2018)
Since October 2004 Tax Office PMA begin implementing Modern System Administration using Information Systems Directorate General of Taxation (DGT). For ease of service and control of the taxpayer and increase productivity apparat, this office is fully supported by computer-based administration system. Aspects of good governance is also applied to improve the quality and certainty and legal equality to the taxpayer. Modern system of tax administration to embrace the latest technological advances with the various modules of office automation are expected to improve control mechanisms more effectively supported by the adoption of a code of ethics officials at the (DGT), which regulates employee behavior in performing the task. So that the benefits to be gained from the implementation of modernization of tax administration system for taxpayers is simplicity, where the workflow is simpler and certainty that there is certainty in implementing tax regulations. Effect Decrease in tax rates, Tax Audit and Organization's Culture against Tax Revenue on the Tax Office of Foreign Investment Two. The purpose of this study was to determine the influence of Decrease in tax rates, Tax Audit and Organization's Culture against Tax Revenue. This research is quantitative method through the survey, with respondents 146 respondents where the participation rate of 99%. Decrease in Tax Rates that will have a positive and significant impact on Tax Revenue. Tax Audit has a positive and significant impact on Tax Revenue. The Organization's Culture has a positive and significant impact on Tax Revenue. Tariff Reduction, Tax Audit and Organizations Culture, has a positive and significant impact on Tax Revenue.Â Â